Caracterização do genoma mitocondrial de onça-pintada (Panthera onca) e elucidação da filogenia mitogenômica do gênero Panthera - Heidtmann, Laura Moretti (2014)
Mitochondrial genomes (mitogenomes) are usually obtained through DNA sequencing produced by a set of conserved PCR primers that are designed to generate overlapping segments, thus completing the whole mitochondrial DNA. This may be a good strategy for some organisms. However, the translocation of cytoplasmic mitochondrial DNA (cymtDNA) into the nuclear genome (numt) is known to be a frequent phenomenon in many taxa, including the felid genus Panthera. Some strategies have been developed to avoid the unwanted amplification of numt, such as mitochondrial isolation followed by PCR or long-PCR. Recently, next-generation sequencing (NGS) approaches have begun to be extensively used in this field. Among these, RNA sequencing (RNAseq) seems to be extremely useful to generate mitogenomes and to avoid numts, as it allows the efficient capture at high coverage of mtDNA transcripts, avoiding pseudogenized nuclear copies. When we initiated this study, mitochondrial genomes of all species of the Panthera genus except the jaguar (P. onca) were available in public databases such as GenBank. Given the importance of this molecular marker for jaguar population studies and for phylogenetic analyses within the Panthera genus, the goals of this project were to (i) characterize the Panthera onca mitogenome, eliminating the possibility of erroneous amplification of numt; and (ii) to conduct the first mitogenomic analysis of the Panthera genus. We have characterized the mitochondrial genome of the jaguar employing RNA-seq data. The transcripts covered about 95% of the mitogenome, with the remaining gaps being complemented by PCR-based DNA sequencing, using specific primers designed for this purpose. All mitogenomic phylogenetic analyses (Maximum Likelihood, Maximum Parsimony, Neighbor-Joining and Bayesian Inference) supported a congruent topology (((N. nebulosa ((P. tigris (P. onca (P. uncia, (P. leo, P. pardus))))). This topology is unprecedented for the genus, but our results indicate that it correctly reflects the evolutionary history of mitochondrial DNA in this group. This study demonstrated that, with RNA-seq approach, almost the entire mitochondrial genome from an individual can be quickly characterized. Furthermore, this approach holds great promise especially in the case of groups plagued by the presence of large and recent numts, as is the case of Panthera species.